Open abdomen in acute mesenteric ischemia - Acosta, Stefan; Kärkkäinen, Jussi (Anestezjologia Intensywna Terapia, 2019)
In acute mesenteric ischemia, early diagnosis should optimally be followed by either open or endovascular intestinal revascularization. All too often, diagnosis is delayed and diagnosis and treatment are performed at the same time during explorative laparotomy. The majority of patients will be diagnosed when transmural intestinal infarction has developed and at this time point damage control strategies involving intestinal revascularization, bowel resection, open abdomen and second look may be necessary to salvage the patient. This review outlines the principles of the damage control surgery approach in acute mesenteric ischemia and the rationale for temporary open abdomen. In patients in need of long-term open abdomen therapy, negative pressure wound therapy with continuous fascial traction is a preferred technique achieving a high delayed fascial closure rate.